Microstructure and properties of SiCw/SiC composites prepared by gel-casting combined with precursor infiltration and pyrolysis. Issue 1 (January 2018) - Chen, Naiqi; Cheng, Laifei; Liu, Yongsheng; Ye, Fang; Li, Mingxing; Gao, Zhiwei; Zhang, Litong
Abstract: Near net-shaped SiCw /SiC composites with higher fracture toughness and isotropic mechanical properties were successfully fabricated by gel-casting combined with precursor infiltration and pyrolysis (PIP). In the gel-casting process, the effects of dispersant dosage, pH value, and solid loading on the rheology of slurries were investigated in detail. A well-dispersed slurry was obtained when the pH was 11 and dispersant dosage was 1.2 wt%. As the solid loading increased from 28 to 40 vol%, the flexural strength of green bodies and SiCw /SiC composites increased from 62.34 and 260.38 to 80.21 MPa and 308.29 MPa, respectively, and the fracture toughness of SiCw /SiC composites increased from 4.56 to 5.32 MPa m 1/2 . However, when the solid loading reached 44 vol%, uneven pores were observed in the green bodies. The highest density and mechanical properties of composites were obtained when the solid loading was 40 vol%. The toughening mechanisms involved were whisker bridging, whisker pull-out and crack deflection.